FEASIBILITY OF LMS-BASED E-MODULES IN COMPUTER NETWORK LEARNING USING THE PROBLEM BASED LEARNING MODEL - Akhmad Tasikun; Basukiyatno; Beni Habibi (SOSIOEDUKASI, 2026)
Vocational education demands interactive digital resources that foster higher-order thinking skills, particularly in practice-oriented subjects like computer networks. However, many current digital tools lack integration with structured pedagogical models. This study aims to develop and evaluate the feasibility of a Learning Management System (LMS) based e-module integrated with the Problem-Based Learning (PBL) model for eleventh-grade computer network learning. Employing a Research and Development design with the ADDIE model, this study focused on the development stage. Participants included material and media experts, informatics teachers, and 72 eleventh-grade students from a public high school, selected via purposive and quota sampling. Data were collected using expert validation sheets and student response questionnaires. The findings demonstrate that the e-module is highly feasible for implementation. Both material and media experts rated the module with an average score of 3.63 (very high), highlighting strong conceptual accuracy, clear instructional design, and excellent visual ergonomics. Furthermore, student responses yielded a highly positive average score of 3.52, indicating strong accessibility and engagement, despite minor challenges in comprehending specific technical terms. In conclusion, the LMS-based e-module successfully synergizes digital learning architecture with the PBL syntax, proving to be a highly feasible pedagogical instrument. Its practical implementation requires complementary cognitive scaffolding to prevent cognitive overload, providing a robust framework for enhancing analytical skills and autonomy in vocational education